Analisis Perancangan Ulang Tata Letak Gudang Menggunakan Metode Dedicated Storage pada PT Bosowa Berlian Motor - Buana, Arga; Vikaliana, Resista (Universitas Batanghari, 2025)
There are problems related to warehouse capacity not being used optimally at PT Bosowa Berlian Motor. This can affect the storage process carried out. Therefore, this research aims to minimize the total distance traveled and total travel time by warehouse employees in carrying out their duties. The data used in this research was obtained from data on incoming and outgoing goods over a 3-months period, namely from July 2023 to September 2023. The existing layout used by PT Bosowa Berlian Motor for storage activities within a period of 3 months selected 34 products that had a frequency biggest. The Dedicated Storage method in this research is used to determine the position of goods stored based on the frequency, distance and capacity of the warehouse used by PT Bosowa Berlian Motor. There are 2 basic classifications of goods stored in warehouses with a total distance traveled under existing conditions, namely 128580m and 56860m. Based on the results of data processing, it was found that the total distance traveled between the proposed layout and the existing layout for KTB products was 77% and for MMKSI products was 8%. Therefore, the proposed layout for PT Bosowa Berlian Motor is good to implement considering the significant increase in efficiency proportions.